Review article: associations between Helicobacter pylori and obesity ‐ an ecological study. Issue 1 (15th May 2014) - Lender, N.; Talley, N. J.; Enck, P.; Haag, S.; Zipfel, S.; Morrison, M.; Holtmann, G. J.
Summary Background There is emerging debate over the effect of Helicobacter pylori infection on body mass index (BMI). A recent study demonstrated that individuals who underwent H. pylori eradication developed significant weight gain as compared to subjects with untreated H. pylori colonisation. Aim To elucidate the association between H. pylori colonisation and the prevalence of overweight and obesity in developed countries. Methods The literature was searched for publications reporting data on H. pylori prevalence rates and obesity prevalence rates. Studies selected reported H. pylori prevalence in random population samples with sample sizes of more than 100 subjects in developed countries (GDP >25 000 US$/person/year). Corresponding BMI distributions for corresponding countries and regions were identified. Nonparametric tests were used to compare the association between H. pylori and overweight and obesity rates. Results Forty‐nine studies with data from 10 European countries, Japan, the US and Australia were identified. The mean H. pylori rate was 44.1% (range 17–75%), the mean rates for obesity and overweight were 46.6 (±16)% and 14.2 (±8.9)%. The rate of obesity and overweight were inversely and significantly (r = 0.29, P < 0.001) correlated with the prevalence of H. pylori infection. Conclusions There is an inverse correlation between H. pylori prevalence and rate of overweight/obesity in countries of the developed world. Thus, the gradual decrease of the H. pylori colonisation that has been observed in recent decades (or factors associated with decrease of) could be causally related to the obesity endemic observed in the Western world.